Empowering digital competence through peer-assisted learning and virtual reality in health professions education - Røe, Yngve; Johansen, Truls Sveløkken; Bruset, Else Britt (Frontiers in Education, 2025)
This study examines the integration of peer-assisted learning (PAL) and virtual reality (VR) gaming in health professions education, focusing on an occupational therapy program in Norway. While PAL is known to enhance clinical skills and knowledge, its role in fostering digital competence has been less explored. This research addresses the gap by investigating how peer assistants perceive their roles and development while integrating VR into health education. Implemented since 2021, the educational approach positions peer assistants as supervisors of VR gaming activities, independent of faculty involvement. Following a rigorous recruitment and training process, a “train-the-trainer” model fosters autonomy, leadership, and collaboration, guided by sociocultural learning theory. Three focus groups with 10 peer assistants revealed evolving teacher identities, technological mindsets, and professional growth. Assistants leveraged their unconventional gaming and technology backgrounds to connect digital tools with healthcare practices, emphasizing the role of reflection in leadership development and career aspirations. The findings highlight the dual impact of PAL and VR in advancing students’ digital competence while empowering peer assistants through professional transformation. Challenges, such as technological hesitancy and gender dynamics, were addressed with inclusive strategies. This study contributes to understanding the integration of digital technologies in health professions education, offering a replicable model to foster digital competence and prepare healthcare professionals for a digitalized landscape. Future research should investigate scalability across disciplines and institutions.